Enhanced Thermal and Antibacterial Properties of Stereo-Complexed Polylactide Fibers Doped With Nano-Silver - Zhao, Shiyou; Ke, Huizhen; Yang, Tingting; Peng, Qiqi; Ge, Jianlong; Yao, Lirong; Xu, Sijun; Zhirong, Ding; Pan, Gangwei (Frontiers in Materials, 2022)
Stereo-complexed polylactide (sc-PLA) fibers with excellent heat resistance and antibacterial properties were prepared by electrospinning. Due to poor heat resistance, common poly(L-lactide) (PLLA) fibers have poor dimensional stability at high temperatures and cannot be sterilized and recycled as a medical filter material. In this research, PLLA/poly(D-lactide) (PDLA) blends doped with silver nanoparticles (AgNPs) were electrospun to obtain the sc-PLA fibers. The effect of thermal induction temperature on the crystalline structure and thermal properties of sc-PLA fibers was investigated. Moreover, the influence of the addition amount of AgNPs on the crystal structure of sc-PLA fibers was studied, and the antibacterial properties of the sc-PLA fibers with different addition amount of AgNPs were analyzed. The thermal induction is beneficial to the formation of stereo-complexed crystals of sc-PLA fibers, and finally completely stereo-complexed PLA fibers was obtained. The melting temperature of the completely stereo-complexed PLA fibers was 50 °C higher than the PLLA fibers, therefore the sc-PLA fibers have better heat resistance. The addition of AgNPs was conducive to the formation of stereo-complexed crystals of sc-PLA fibers. In addition, the antibacterial rate of sc-PLA fibers against E-coli and S. aureus was 99.99±0.01% respectively when the addition amount of AgNPs was only 0.15 wt%. Fiber membrane obtained in this experiment as a reusable filter material, and the sc-PLA fiber membrane has broad application prospects in the biomedical field.